Avaliação do efeito provocado pela presença de furos em uniões metálicas com adesivo acrílico - Koppe, Rafael (2014)
This paper presents a study of the insertion of holes in the overlap area of bonded joints as an alternative to the conventional methods of surface preparation in order to increase the mechanical strength by increasing the anchorage on the bond process. This study evaluated the mechanical strength to static loading by a factorial experiment, and for the evaluation of the resistance to dynamic load, a Wöhler s curves was made for the respective treatments. Through this study we concluded that with the static loading condition, the insertion of holes is not an effective alternative and in some cases it may be harmful. The dynamic loading study detected a slight improvement in performance by the specimen with holes in the overlapping region.